Adaptive robust position control scheme for an electromagnetic levitation system with experimental verification - Ziwei Wu; Kuangang Fan; Ping Yi (PLoS ONE, 2025)
Electromagnetic levitation technology has several advantages, such as no friction, safety, and reliability. Electromagnetic levitation control, as the core of electromagnetic levitation technology, has attracted people’s attention. The use of other traditional control algorithms frequently results in a decline in the system’s anti-disturbance and tracking performance due to the highly nonlinear, stochastic uncertainty, and time delay characteristics of electromagnetic levitation systems. This work takes the single point electromagnetic levitation ball system as the research object to address the above-mentioned issues. A control method combining an improved whale optimization algorithm with robust sliding mode control and adaptive linear active disturbance rejection (IWOA-SMC-ALADRC) is proposed to achieve stable control of a single point electromagnetic levitation ball. Firstly, a nonlinear model of the electromagnetic levitation ball system was established; Secondly, robust sliding mode control is combined with linear active disturbance rejection control, and an adaptive parameter tuning strategy is introduced for the PD module in LADRC; Meanwhile, an improved whale optimization algorithm was proposed to address the issue of excessive adjustable parameters in the controller; In addition, the stability and convergence of the control algorithm were proven using the Lyapunov equation; Finally, in order to verify the effectiveness of the control method, PID, LADRC, CS-LADRC, and I-LADRC were introduced for simulation analysis and experimental verification. The results indicate that IWOA-SMC-ALADRC has better anti-disturbance and tracking performance.